Childhood glaucoma surgery in the 21st Century - Papadopoulos, M (Nature Publishing Group, 2014)
Most children with glaucoma will require surgery in their lifetime, often in their childhood years. The surgical management of childhood glaucoma is however challenging, largely because of its greater potential for failure and complications as compared with surgery in adults. The available surgical repertoire for childhood glaucoma has remained relatively unchanged for many years with most progress owing to modifications to existing surgery. Although the surgical approach to childhood glaucoma varies around the world, angle surgery remains the preferred initial surgery for primary congenital glaucoma and a major advance has been the concept of incising the whole of the angle (circumferential trabeculotomy). Simple modifications to the trabeculectomy technique have been shown to considerably minimise complications. Glaucoma drainage devices maintain a vital role for certain types of glaucoma including those refractory to other surgery. Cyclodestruction continues to have a role mainly for patients following failed drainage/filtering surgery. Although the prognosis for childhood glaucoma has improved significantly since the introduction of angle surgery, there is still considerable progress to be made to ensure a sighted lifetime for children with glaucoma all over the world. Collaborative approaches to researching and delivering this care are required, and this paper highlights the need for more high-quality prospective surgical trials in the management of the childhood glaucoma.